2020
DOI: 10.1155/2020/5862645
|View full text |Cite
|
Sign up to set email alerts
|

Lysine Reacts with Cholesterol Hydroperoxide to Form Secosterol Aldehydes and Lysine-Secosterol Aldehyde Adducts

Abstract: Two cholesterol secosterol aldehydes, namely, 3β-hydroxy-5-oxo-5,6-secocholestan-6-al (secosterol A) and its aldolization product 3β-hydroxy-5β-hydroxy-B-norcholestane-6β-carboxyaldehyde (secosterol B), are highly bioactive compounds which have been detected in human tissues and potentially contribute to the development of physiological dysfunctions such as atherosclerosis, Alzheimer’s disease, diabetes, and cancer. They were originally considered to be exclusive products of cholesterol ozonolysis and thus to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…462 Amides such as 94 have been detected during the photosensitized oxidation of cholesterol and are proposed to form via oxidation of the hemiaminal intermediate formed by the reaction of the terminal amino group of lysine with the aldehyde group of 93. 437 Formation of Schiff bases between cholesterol aldehydes and proteins leads to changes in protein folding that are potentially important in the development of disease. 453,463 Ketosterols are generally unreactive toward Schiff base formation.…”
Section: Cholesterolmentioning
confidence: 99%
See 2 more Smart Citations
“…462 Amides such as 94 have been detected during the photosensitized oxidation of cholesterol and are proposed to form via oxidation of the hemiaminal intermediate formed by the reaction of the terminal amino group of lysine with the aldehyde group of 93. 437 Formation of Schiff bases between cholesterol aldehydes and proteins leads to changes in protein folding that are potentially important in the development of disease. 453,463 Ketosterols are generally unreactive toward Schiff base formation.…”
Section: Cholesterolmentioning
confidence: 99%
“…These can be formed by a number of routes, including ozonolysis, reaction of cholesterol with 1 O 2 , and Hock rearrangement of the α-isomer of 85 . Amides such as 94 have been detected during the photosensitized oxidation of cholesterol and are proposed to form via oxidation of the hemiaminal intermediate formed by the reaction of the terminal amino group of lysine with the aldehyde group of 93 …”
Section: Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although it has been suggested that such carbonylation involves hydroxyl radicals generated by the Fenton reaction between hydrogen peroxide and ferrous ions [ 48 ], this is unlikely due to the very high reactivity of hydroxyl radicals, which makes them react unselectively [ 50 ]. Singlet oxygen ( 1 O 2 ) is a more selective ROS, which can be formed by the reaction of hydrogen peroxide with glucose [ 51 ], oxidizes amines [ 52 ], and such oxidation was recently suggested as being involved in the formation of biologically relevant amide-type adducts such as N ε -(hexanoyl) lysine [ 53 ]. Thus, it is proposed that the carbonylation of Na + /K + ATPase may be mediated by singlet oxygen according to Figure 3 .…”
Section: Isolated Alpha Cells Exhibit a V-shaped Glucagon Secretiomentioning
confidence: 99%